Chasing the Sun - Peterson, Tracie (Minneapolis : Bethany House, 2012)
Desperate for help to run the ranch that her missing father recently acquired on the Texas plains, Hannah Dandridge forms an uneasy truce with William Barnett, who is desperate to regain his family's land--the ranch that Hannah is struggling to keep running.
Keywords: Texas -- Fiction -- History -- 19th century; United States -- Fiction -- History -- 1861-1865, Civil War; Christian fiction; Love stories